Aplicación del método de coagulación de plasma al estudio ultraestructural de especímenes biológicos - Hernández, Francisco (Universidad de Costa Rica, 1991)
Biological particulate specimens, ineluding Saccharomyces cerevisiae yeast, bovine spermatozoa and human blood cells (normal erytrocites and leukemic cells) were processed for scanning an,d transmission electron microscopy using the coagulated plasma technique. The specimens were suspended in frozen and thawed plasma; later, coagulation was induced by adding CaCI2. The elot was cut into small pieces and processed as tissue fragments. The technique is an useful tool when processing biological particulate specimens for electron microscopy.